2023
DOI: 10.3390/ijerph20032757
|View full text |Cite
|
Sign up to set email alerts
|

Is It Time to Re-Shift the Research Agenda? A Scoping Review of Participation Rates in Workplace Health Promotion Programs

Abstract: Workplace health promotion programmes (WHPPs) are among the most important measures to improve the health and motivation of the ageing workforce. However, they are accompanied with certain challenges, such as low participation rates and higher participation levels of the more health-conscious workers, often failing to engage those who need such interventions the most. Following the PRISMA guidelines, this scoping review examined participation rates reported in articles on WHPPs to identify potential knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…However, it is not possible to draw any conclusions in this respect based on the data of the current study. A literature review showed that participation rates in workplace health promotion programs are generally low, especially among those who need them most: rates typically range between 20 and 30% [30], which is comparable to the rates found in the current study (Army Staff 43.3%, Central Staff 15.8%, Airforce Staff 32.6%). The low participation rates could be caused by several reasons.…”
Section: Discussionsupporting
confidence: 83%
“…However, it is not possible to draw any conclusions in this respect based on the data of the current study. A literature review showed that participation rates in workplace health promotion programs are generally low, especially among those who need them most: rates typically range between 20 and 30% [30], which is comparable to the rates found in the current study (Army Staff 43.3%, Central Staff 15.8%, Airforce Staff 32.6%). The low participation rates could be caused by several reasons.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, they highlighted the inclusion of incentives, feedback, competitive challenges, and monthly workshops as implementation strategies to increase employee engagement in these programs. Bensa and Sirok [43] most recently emphasized the need to identify determinants of participation in these programs to better target specific subgroups who may not participate in these programs. We believe such a focus could be beneficial in targeting the participation of parents with several young children.…”
Section: Discussionmentioning
confidence: 99%
“…Most evaluation research in health promotion focuses on the effectiveness of programs, neglecting the reach and enrollment of participants [29][30][31]. When reach is assessed, researchers often only provide numbers and general characteristics of participants, without providing insight into the underlying factors that influence participation [32].…”
Section: Introductionmentioning
confidence: 99%